BUDIDAYA IKAN LELE DENGAN KOLAM TERPAL DI KELURAHAN KEPUTIH KECAMATAN SUKOLILO KOTA SURABAYA: CATFISH FARMING WITH TARPAULIN POND IN KEPUTIH VILLAGE, SUKOLILO DISTRICT, SURABAYA CITY - Sulestiani, Aniek; Aprilia, Shevick; Tri Putra, Satria Rizal; Hari Subagio; Mochamad, Arief Sofijanto (Universitas Hang Tuah Surabaya, 2025)
Sukolilo district faces significant problems in catfish cultivation, especially related to the use of tarpaulin ponds as a cultivation medium. Technical constraints experienced by the community include ph, temperature, and tarpaulin pond management. The community service activities of the hang tuah university surabaya faculty of engineering and marine science team have the aim of educating and empowering the community in utilizing catfish cultivation by optimizing tarpaulin materials. The method is in the form of land preparation, making ponds with tarpaulins, preparing needs stage, hatchery implementation stage observation of cultivation implementation and marketing, with training and counseling. The final result of this community service activity is that the economic potential in keputih village, sukolilo district can be raised by optimizing catfish farming activities with tarpaulins.